Structural, Optical and Electrical Properties of Ruddlesden Popper Oxide Ba2SnO4 - Kumar U.; Upadhyay S. (My University, 2025)
A study of structural, optical and electrical properties have been investigated in this paper. The powder and ceramic of Ruddlesden popper oxide Ba2SnO4 are prepared by the solid state ceramic route. Single phase of Ba2SnO4 has been obtained by calcination at 1000°C for 8 h. Rietveld refinement of powder x-ray diffraction data indicated the tetragonal crystal structure of calcined powder with lattice constants a = b = 4.1458 Å, c = 13.2899 Å. Further, the phase identification of powder is studied by Fourier transform infrared and Raman spectroscopy. Analysis of the obtained powder by transmission electron microscope reflected the spherical shape of the particle in the range (74 ± 8) nm. AC conductivity of ceramic follows the universal power law, σ=σdc[1+(ffH)n]. Temperature dependence behaviour of dc conductivity (σdc) and hopping frequency (fH) indicated that the origin of dc conduction and ac conduction mechanisms are similar. Conductivity spectra at different temperatures scaled by Ghosh scaling σ′(f)σdc=F(ffH) perfectly follows the time temperature superposition principle. X-ray photoelectron spectroscopy analysis of ceramic indicated the presence of Ba in Ba2+, Sn in Sn4+ and Sn2+ and oxygen vacancies in the sample. Thermal expansion coefficient of the prepared ceramic is found to be 3.44 × 10−6/°K. © 2019, The Minerals, Metals & Materials Society.